Study on comparative analysis of basic woven fabrics produced in air-jet loom and determining structure for optimum mechanical properties and production - Nurunnabi, Md (Array, 2020)
This analysis was directed at dissecting the impact of the structure of the fabric on different properties of the fabric, for example tear strength, tensile strength, shrinkage, elongation, skewness, and so on. The work demonstrated how various structures of the fabric influence these properties. Fabrics with a fundamental woven structure, namely plain, twill, satin and a couple of their subsidiaries, were produced to explore the influence of the structure on different properties of the fabric. The examination built up an approach to gauge the mechanical conduct of the fabric dependent on its structure. The exploration accentuated the structure and detail of the fabric to decide the underlying driver of the change in the mechanical conduct. The properties of the fabric, such as tear strength, tensile strength, elongation, shrinkage and skewness, were extraordinarily affected by the structure of the fabric. It likewise demonstrated to having more noteworthy mechanical properties for firmly interwoven structures, such as plain and twill. The analysis led to the conclusion that the plain structure has the best mechanical properties among different structures.